(untitled) (Italian Journal of Public Health, 2011)
Background: Influenza vaccination coverage among healthcare workers (HCWs) is unacceptably low despite the recommendations of health authorities. Objective: The aim of the study is to assess the knowledge base of healthcare workers in Local Health Services (LHS) regarding influenza vaccination and to identify the factors that inhibit or motivate vaccination among HCWs. Methods: A cross sectional study was carried out between July and October 2003 within the five Hospitals of the LHS “Azienda Sanitaria Salerno2”, Salerno, Italy. In July 2003, we prepared a standardized anonymous questionnaire for a sample of 280 healthcare workers aimed at surveying their knowledge base and attitudes towards influenza and vaccination. The HCWs were recruited by random selection using the stratified layered sampling method. On the basis of the results of our survey, a hospital vaccination campaign was undertaken. Statistical analysis was carried out using the EpiInfo 6.06 program. Data were analyzed through frequency distribution. Statistical comparison was performed using the Chi-square tests and a p-value <0,05 was considered statistically significant*. Results: During the 2003-2004 influenza season, 230 (81%) out of 280 employees answered the questionnaire. 31 respondents (13.5%) were physicians, 94 (40.9%) were nurses and 105 (45.6%) were workers employed in supporting services. The vaccination rate among Health Care workers of this Local Health Service (LHS) unit was about 15.0%. The reasons most frequently cited by HCWs for noncompliance with vaccination were confidence in their own personal health, the fear of adverse reactions to the vaccine and the doubt they had about vaccine efficacy. Conclusions: We conclude that those responsible for influenza vaccination programs might consider a specifically tailored intervention strategy aimed at improving coverage. The answers collected can be used to refine the following season’s campaign.